2008
DOI: 10.1007/s00265-008-0634-0
|View full text |Cite
|
Sign up to set email alerts
|

Why do not all workers work? Colony size and workload during emigrations in the ant Temnothorax albipennis

Abstract: Here, we study distribution of workload and its relationship to colony size among worker ants of Temnothorax albipennis, in the context of colony emigrations. We find that one major aspect of workload, number of items transported by each worker, was more evenly distributed in larger colonies. By contrast, in small colonies, a small number of individuals perform most of the work in this task (in one colony, a single ant transported 57% of all items moved in the emigration). Transporters in small colonies carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 55 publications
4
55
2
Order By: Relevance
“…Differences at the colony level were underpinned by variation in individual behaviour between emigration distances. The finding that individual tandem running workload (leading and following tandem runs) decreased with the number of ants actively engaged (Figs 5 and 2D) is consistent with observations in analogous systems, and constitutes a commonly observed phenomenon in insect societies (Karsai and Wenzel, 1998;Dornhaus et al, 2008). Principally, the decrease in individual contributions when more ants are engaged may be explained by the reduced need for workers to be involved in a task, and the concomitant reduction in task stimuli (PinterWollman et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Differences at the colony level were underpinned by variation in individual behaviour between emigration distances. The finding that individual tandem running workload (leading and following tandem runs) decreased with the number of ants actively engaged (Figs 5 and 2D) is consistent with observations in analogous systems, and constitutes a commonly observed phenomenon in insect societies (Karsai and Wenzel, 1998;Dornhaus et al, 2008). Principally, the decrease in individual contributions when more ants are engaged may be explained by the reduced need for workers to be involved in a task, and the concomitant reduction in task stimuli (PinterWollman et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…The relative likelihood and significance of such options is uncertain, as previous studies have shown complex and differing structures of work distribution within colonies. Many of the studies conducted to date support the concept that T. albipennis colonies have some 'specialist' workers in relation to certain task groups (Dornhaus, 2008;Dornhaus et al, 2008). It has been noted that task propensities are positively correlated within groups of related tasks, e.g.…”
Section: Introductionmentioning
confidence: 85%
“…This is likely consistent with what has been observed in real ant colonies [4], where even during periods where tasks have a very high demand (such as nest migration) an important fraction of the ants remain idle where the rest perform the tasks necessary for the survival of the colony.…”
Section: Task Assignmentsupporting
confidence: 77%
“…We will say an ant is idle at time t if it belongs to the set I(t) 4 . For succinctness we define the energy supply and the energy need at each task (both are defined in terms of a task assignment).…”
Section: Task Assignmentmentioning
confidence: 99%
“…For cavity-nesting ants, scouts sense quorum by spending 1-2 minutes in a nest assessing the number of workers present via encounter rate, rather using than indirect cues such as pheromone concentration [34] [31]. Quorum threshold as a proportion of colony size is remarkably constant across a range of colony sizes (c3.5%) [13], and this is intriguing, because the relationship between colony size and cavity size is not simple positive correlation: although larger colonies do inhabit larger cavities in the wild, in laboratory tests both small and large colonies prefer larger cavities, presumably to allow for growth [33], [11] & [22].…”
Section: Quorum Sensing In House-hunting Antsmentioning
confidence: 99%